2020
DOI: 10.3390/ijerph17145014
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Sun Exposure Has Become a Real Public Health Problem

Abstract: This article aims to alert the medical community and public health authorities to accumulating evidence on health benefits from sun exposure, which suggests that insufficient sun exposure is a significant public health problem. Studies in the past decade indicate that insufficient sun exposure may be responsible for 340,000 deaths in the United States and 480,000 deaths in Europe per year, and an increased incidence of breast cancer, colorectal cancer, hypertension, cardiovascular disease, metabolic syndrome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 105 publications
(137 reference statements)
3
118
0
Order By: Relevance
“…Sunlight exposures have also positive effects on human health ( Alfredsson et al, 2020 ). Suitable sunlight exposure is essential for vitamin D synthesis, which is involved in several physiological functions ( Föcker et al, 2017 ).…”
Section: Brain Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sunlight exposures have also positive effects on human health ( Alfredsson et al, 2020 ). Suitable sunlight exposure is essential for vitamin D synthesis, which is involved in several physiological functions ( Föcker et al, 2017 ).…”
Section: Brain Plasticitymentioning
confidence: 99%
“…However, insufficient sunlight exposure along with a low status of vitamin D may be responsible for critical public health issues and neuropsychiatric disturbances such as cardiovascular diseases, metabolic syndrome, hypertension, multiple sclerosis, asthma, type 1 diabetes, autism, Alzheimer's disease, schizophrenia and depression ( Alfredsson et al, 2020 ; Brouwer-Brolsma et al, 2013 ; Föcker et al, 2017 ; Humble et al, 2010 ; Itzhaky et al, 2012 ). Accordingly, it was demonstrated that adults with depression exposed to low sunlight showed a decrease in interleukin-6 (IL-6) serum levels, a pro-inflammatory cytokine, when compared to adults with depression who were exposed to high sunlight ( Levandovski et al, 2013 ), which supports the well described benefits of proper sunlight exposition ( Alfredsson et al, 2020 ). Also, there was already observed that increased serum levels of IL-6 during childhood have been associated with a greater risk of developing depression and psychosis in young adulthood ( Khandaker et al, 2014 ).…”
Section: Brain Plasticitymentioning
confidence: 99%
“…Exposure to sunlight has many effects on human health (1) including erythema (sunburn), skin cancer, and vitamin D synthesis. Until recently, vitamin D synthesis was regarded as the only benefit from solar exposure, but there is increasing evidence for other health benefits that are independent of vitamin D, (1,2) such as reduced blood pressure. (3)(4)(5) All UVR effects are initiated by the absorption of UVR by chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies showing the vitamin D importance in prevention of various cancers such as breast, colon, prostate [7], and several other cancers [8]. In the recent years it has been widely discussed that skin cancer prevention should be balanced with spending time outdoors [9,10], as it may have a greater positive role than just vitamin D synthesis [11,12]. Very recently, a link of the serum vitamin D level with severity of COVID-19 infection is a widely discussed issue [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Both studies showed that there is a great risk of overexposure in these regions. This problem concerns not only the occupational overexposures, but it may also appear during tourist cruises, which became a popular Atmosphere 2021, 12, 474 2 of 12 way of spending leisure time in the high latitude regions (e.g., the summer Hurtigruten Norwegian costal voyages, which contrary to whole-year cruises attract also young people).…”
Section: Introductionmentioning
confidence: 99%